A research update on correlates of heavy episodic drinking among undergraduate college students. - Montauti, Sara; Bulmer, Sandra Minor (American Journal of Health Education, 2014)
Despite prevention efforts of colleges and universities across the nation, there have been no substantial decreases in heavy episodic drinking among undergraduates over the past 2 decades.This study provides an update on correlates of heavy episodic drinking for a recent cohort of undergraduate college students.A cross-sectional survey design was utilized. Participants were randomly selected undergraduate students from a public 4-year university located in the Northeast.Heavy episodic drinking was associated with male gender, white race, having a family history of drug or alcohol abuse, smoking cigarettes, and using marijuana. Age, athlete status, completion of an alcohol education program, condom use, depression, anxiety, and financial stress were not associated. After controlling for gender and race, marijuana use and smoking cigarettes were found to increase predictability of heavy episodic drinking.Rates of heavy episodic drinking remain high but correlates may be shifting for this cohort of college students. Opportunities to address heavy episodic drinking concurrently with cigarette smoking and marijuana use should be explored.Qualitative research methods are needed to gain insight into reasons for heavy episodic drinking; information that could inform the creation of more effective programming. © 2014 Copyright © SHAPE America.
Keywords: dept.hhs

The impact of caloric information on college student's fast food purchasing intentions - Zigmont, Victoria A; Bulmer, Sandra Minor (American journal of health education, 2015)
Background: Fast food establishments are available on many college campuses and, as a result, many students consume foods that are high in calories and contribute to unhealthy weight gain. Purpose: This study measured college students' knowledge of the calorie content for fast food items and whether the provision of calorie information for those foods influenced their future purchasing intentions. Method: Randomly selected undergraduate college students (N = 201) completed an online survey that measured baseline knowledge of calorie content for a fast food item and intention to purchase that item in the future. After provision of accurate calorie information, students were posttested for intention to purchase that item in the future. Results: The majority of students underestimated calorie content for fast food items. After receiving accurate calorie information, those who initially underestimated calorie content were significantly more likely to change their intention to purchase that food item in the future. Discussion: Many college students are interested in avoiding high-calorie fast food items but are uninformed about calorie content. Translation to Health Education Practice: Colleges should provide calorie information for fast food items at the point of purchase so that students can make informed decisions that will promote their health. © 2015, Copyright © SHAPE America.
Keywords: dept.hhs; dept.pch

Young women's experiences living with polycystic ovary syndrome - Weiss, Theresa R.; Bulmer, Sandra Minor (JOGNN - Journal of Obstetric, Gynecologic, and Neonatal Nursing, 2011)
Objective: To explore the psychosocial effects of living with polycystic ovary syndrome (PCOS) through the experiences of young women diagnosed with this endocrine disorder. Design: A qualitative, phenomenological methodology was used. Data were obtained through personal, semistructured interviews. Setting: College campuses in New England. Participants: A purposive sample of 12 young women with PCOS age 18 to 23 years. Results: The following themes emerged from analysis of participants' responses: concerns for older self, feeling physically inferior, coping with symptoms, patient-provider relationship, seeking useable information and support, and coming to terms with a chronic condition. Conclusions: Participants in this study faced numerous physical, social, and emotional challenges on a daily basis. As these young women gathered information relevant to their needs, sought and received social support, and maintained their daily routines to improve their health and appearance, they came to terms with this chronic condition. Based on participants' relayed experiences, it became evident that a need exists for health care practitioners to include psychosocial support in a comprehensive holistic plan for the treatment of PCOS in adolescents and young women in their early twenties. JOGNN, 40, 709-718; 2011. DOI: 10.1111/j.1552-6909.2011.01299.x
Keywords: Adaptation, Physiological; Adaptation, Psychological; Adolescent; Adolescents; Age Factors; Attitude to Health; Cross-Sectional Studies; Female; Humans; Interpersonal Relations; Interviews as Topic; Lived experience; New England; PCOS; Polycystic Ovary Syndrome; Polycystic ovary syndrome; Psychosocial; Qualitative; Quality of Life; Quality of life; Risk Assessment; Self Concept; Severity of Illness Index; Social Support; United States; Urban Population; Young Adult; Young women; adaptation; adaptive behavior; adolescent; adult; age; article; attitude to health; comparative study; cross-sectional study; dept.hhs; female; hospitalization; human; human relation; interview; ovary polycystic disease; psychological aspect; quality of life; risk assessment; self concept; social support; urban population

Using cognitive mapping to explore women caregivers' experiences - Valentino, Carmela Cassisi; Bulmer, Sandra Minor (American Journal of Alzheimers Disease and Other Dementias, 2005)
Women are often faced with the primary role of providing care for individuals with Alzheimer's disease (AD). This study explored women caregiver's perceptions of caregiving through the use of Cognitive Mapping (CM), a qualitative research method. Volunteers were recruited from caregiver support groups to construct maps of their experience of "caregiving for someone with AD." Maps were analyzed for commonly identified concepts and relationships. Twelve participants identified 280 concepts, 206 of which were unduplicated. Concepts were collapsed into 17 categories; the largest concepts being "friends and family," "sad," "frustration," and "time." The maps produced by the sample in this study were unique, providing evidence that the experience of AD caregiving varies significantly among caregivers. CM appears to be effective for identifying caregiver stressors and needed support services.
Keywords: Alzheimer disease; Alzheimer's disease; Caregivers; Cognitive mapping; Experience; Women; adult; article; brain function; caregiver; cognition; cognitive mapping; concept analysis; dept.pch; experience; family; female; friend; frustration; human; human experiment; loneliness; normal human; patient care; qualitative analysis; social support; stress; time

Women's perceived benefits of exercise during and after breast cancer treatment. - Bulmer, Sandra Minor; Howell, Jeremy; Ackerman, Louise; Fedric, Regan (Women & Health, 2012)
Empirical data support the benefits of physical activity for women who have been diagnosed with breast cancer. However, the experience of exercising during or after breast cancer treatment has not been fully documented. The purpose of the researchers in this study was to provide an in-depth description of women's experiences with exercising during or after their breast cancer treatments, specifically, their perceptions of the benefits they experienced as a result of participation in an individualized exercise program that included cardiovascular and resistance activities. Forty-five women who had been diagnosed with breast cancer within the previous two years were recruited from two oncology practices after electing to enroll in an exercise program. Data were collected between September 2006 and August 2007 through in-depth interviews at various stages in the exercise program and analyzed simultaneously using thematic analysis methods. Whether in treatment or post-treatment, women attributed psychological, physical, and social benefits to their participation in the exercise program. Participants credited the program with helping them to feel better, regain control over their bodies and their lives, manage their emotions, and prepare them to live healthfully going forward. These results provide insight into the specific ways women experience exercise during and after their breast cancer treatments.
Keywords: *Adaptation, Psychological; *Breast Neoplasms/px [Psychology]; *Exercise Therapy/px [Psychology]; *Resistance Training; Adaptation, Psychological; Adult; Breast Neoplasms; Breast Neoplasms/di [Diagnosis]; Breast Neoplasms/rh [Rehabilitation]; Breast Neoplasms/th [Therapy]; Exercise Therapy; Female; Health Care Surveys; Health Services Accessibility; Humans; Interviews as Topic; Middle Aged; Perception; Physical Fitness; Qualitative Research; Questionnaires; Resistance Training; San Francisco; Social Support; Stress, Psychological; Stress, Psychological/px [Psychology]; Surveys and Questionnaires; United States; adaptive behavior; adult; article; breast cancer; breast tumor; dept.hhs; exercise; female; fitness; health care delivery; health care survey; human; interview; kinesiotherapy; mental stress; middle aged; perception; psychological aspect; psychosocial; qualitative research; questionnaire; resistance training; social support; women's health

Ten-year trends and differences in alcohol consumption among black and white female undergraduates - Barton, Barbara A; Bulmer, Sandra Minor; Mugno, Raymond; Misencik, Leann (Journal of Substance Use, 2019)
Background: Few studies have explored changing patterns of alcohol consumption among young females and differences based on race/ethnicity. Objective: This study examined differences in alcohol consumption between black and white undergraduate females and compared trends in three different measures of alcohol consumption over a 10-year period from 2004 to 2014. Methods: The CORE Alcohol and Drug Survey was used to collect data from female undergraduates attending a public university in the northeastern USA. Classes were randomly selected into the sample; class acceptance was 68% and student participation was 96%. The chi-square test examined differences between groups and the Cochrane Armitage Test for Trend assessed changes over time. Results: In 2014, for every measure of alcohol consumption examined, a significantly larger percentage of white females engaged in the behavior compared to black females. Trend analysis from 2004 to 2014 demonstrated a narrowing of this gap. Controlling for age, any alcohol use in past 30 days and binge drinking in the past 2 weeks increased significantly for black females 21 years or older. Any alcohol use in the past 30 days decreased significantly for white females under 21 years. Conclusion: These findings introduce many questions which should be explored through additional research.
Keywords: Alcohol; Article; Black person; Caucasian; United States; adult; alcohol; alcohol consumption; binge drinking; college females; dept.hhs; dept.mat; dept.pch; drinking trends; female; human; major clinical study; peer-reviewed; priority journal; race difference; undergraduate student

Trends in alcohol consumption among undergraduate students at a northeastern public university, 2002-2008. - Bulmer, Sandra Minor; Irfan, Syed; Mugno, Raymond; Barton, Barbara; Ackerman, Louise (Journal of American college health : J of ACH, 2010)
OBJECTIVE: This study examined alcohol consumption patterns and trends at a public university in the Northeast from 2002 to 2008., PARTICIPANTS: Stratified random sampling was used to select undergraduate students enrolled in courses during spring semesters in 2002, 2004, 2006, and 2008., METHODS: Data were collected during regularly scheduled classes for 4 measures of alcohol consumption and 5 demographic categories using the Core Alcohol and Drug Survey., RESULTS: Four groups showed significant increases in both frequency and volume of alcohol consumption-students who were female, over 21 years of age or over, living off-campus, or performing well academically. There were no decreasing trends for any demographic group. These results differ from national college health surveys, which have shown alcohol use remaining steady during this period., CONCLUSIONS: Campus-specific trend data can provide unique perspectives and guide programming efforts. These trends suggest a need for new intervention strategies on this campus.
Keywords: *Alcohol Drinking/ep [Epidemiology]; *Public Sector/sn [Statistics & Numerical Data]; *Students/sn [Statistics & Numerical Data]; *Universities/sn [Statistics & Numerical Data]; Alcohol Drinking; Alcohol consumption; College; Connecticut; Data Collection; Drinking; Female; Humans; Male; Public Sector; Risk-Taking; Statistics, Nonparametric; Students; Trends; United States; Universities; Young Adult; adult; article; dept.mat; dept.pch; drinking behavior; female; high risk behavior; human; information processing; male; nonparametric test; organization and management; peer-reviewed; statistics; student; university

Substance use, anxiety, and depressive symptoms among college students - Walters, Kenneth S.; Bulmer, Sandra Minor; Troiano, Peter F.; Obiaka, Uzoma; Bonhomme, Rebecca (Journal of Child & Adolescent Substance Abuse, 2018)
Research on college substance use and mental illness is limited and inconsistent. Measures of substance use, and anxiety and depressive symptoms, were completed by 1,316 undergraduates within a major drug transportation corridor. Hierarchical linear regressions were used to test associations between anxious and depressive symptoms and substance use (i.e., alcohol, cannabis, tobacco, cocaine, other amphetamines, sedatives, hallucinogens, and designer drugs). Depressive symptoms were associated with use of cannabis, tobacco, amphetamines, cocaine, sedatives, and hallucinogens. Anxiety symptoms were unrelated to substance use. These findings support the need for education and prevention at universities, emphasizing tobacco, cannabis, and certain “harder” drugs.
Keywords: anxiety; college students; depression; dept.hhs; dept.psy; mental health; peer-reviewed; substance use

Using CBPR methods in college health research exploring excessive alcohol consumption - Bulmer, Sandra Minor; Barton, Barbara A; Liefeld, Julie; Montauti, Sara; Santos, Stephanie; Richard, Melissa; Hnath, Laura; Pelletier, Kara; Lalanne, Jude (Journal of Adolescent Research, 2016)
Community-based participatory research (CBPR) is a collaborative methodology that uniquely involves stakeholders in all stages of the research process. CBPR has been widely utilized in the field of public health, but not widely employed with college populations. This study utilized CBPR methods within a college community to gain insight into excessive alcohol consumption. Six student researchers planned and carried out a rigorous qualitative study at a public university in the Northeast region of the United States. A total of 48 undergraduate participants were recruited for focus groups that were facilitated by two student researchers, and transcribed and analyzed using thematic analysis methods. Students' reasons for drinking alcohol were focused within the themes of inclusion, habitual default, and the student development process. Social media, strict policy/enforcement, and student's desire to avoid responsibility led to increased risk and consequences related to drinking. Students recommended late night transportation and a Good Samaritan policy as strategies to improve student safety. This study led to student advocacy and policy change directed at improving student's health and safety and demonstrated that CBPR methods show promise for engaging students and producing meaningful data.
Keywords: college issues; dept.hhs; dept.mft; emerging adulthood; health; qualitative methods; substance use